In silico design of an immunogen against Acinetobacter baumannii based on a novel model for native structure of Outer membrane protein A. (April 2017) - Jahangiri, Abolfazl; Rasooli, Iraj; Owlia, Parviz; Fooladi, Abbas Ali Imani; Salimian, Jafar
Abstract: Outer membrane protein A (OmpA) is the most promising vaccine candidate against one of the most successful nosocomial pathogens, A. baumannii . Despite advantages of the antigen, its cytotoxicity could be considered as a challenge in clinical trials. In order to improve this effective immunogen, rational vaccine design strategies such as structure-based vaccinology should be assessed. However, native structure of OmpA remains controversial. The present study is conducted to address the native structure of OmpA; then, a novel immunogen with lower toxicity and higher antigenicity was designed based on structural vaccinology. Various bioinformatic and immunoinformatic tools were harnessed to perform analyses such as topology, secondary structure, and tertiary structure predictions as well as B-cell epitope predictions. A novel 12-stranded model is suggested for OmpA. K320 and K322 were substituted by Alanine, "NADEEFWN" sequence was replaced by "YKYDFDGVNRGTRGTSEEGTL", Position 1–24 at the N-terminus and the C-terminal sequence "VVQPGQEAAAPAAAQ" were removed. The designed construct has more epitope density and antigenic properties with higher immunogenicity while its cytotoxicity is decreased. Moreover, this single cross-protective antigen could trigger antibodies rendering protection against two important nosocomial pathogens i.e. Pseudomonas aeruginosa and A. baumannii . Highlights: A novel 12-stranded model is proposed for native structure of OmpA in A. baumannii . The model is closer to the experimental evidence reported on OmpA structure. A novel immunogen is designed with decreased cytotoxicity. The immunogen has increased epitope density, antigenicity and immunogenicity. This antigen could trigger antibodies against both P. aeruginosa and A. baumannii .